Non-vitamin K oral anticoagulants (NOACs) in patients with stroke and atrial fibrillation - Jovanović, Dejana (Archives of Pharmacy, 2020)
Patients with atrial fibrillation who had a previous transient ischemic attack or ischemic stroke had a significantly high risk of stroke recurrence and the introduction of oral anticoagulants should be mandatory. However, the long-term use of oral anticoagulants increases the risk of developing all types of intracranial hemorrhages. The advantages of non-vitamin K oral anticoagulants (NOACs) compared to warfarin are that they have a significantly lower risk for hemorrhagic stroke. They are preferred in elderly patients, those with small vessel disease, or those with previous intracerebral hemorrhage. The time of NOACs introduction after an ischemic stroke depends on its severity and the rule “1-3-6-12” days should be applied. The reintroduction of NOACs in patients with atrial fibrillation and previous intracerebral hemorrhage depends on its etiology and should be after about 4-8 weeks if the cardioembolic risk is high and the risk for intracranial hemorrhage small.
Keywords: Ischemic stroke; Intracranial hemorrhage; non-vitamin K oral anticoagulants; atrial fibrillation